Improving Parents Social Stimulations Skills In Assisting Children With Speech Delay Through Content Mastery Service - Syafira Anggraini; Ade Chita Putri Harahap (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This research was grounded on the crucial role of parents in supporting the social and language development of children with speech delay. Speech delay refers to a condition in which a child’s language abilities do not meet age expectations, often requiring early intervention. One effective intervention is content mastery services, provided by counselors or psychologists, which equip parents with strategies to stimulate social interactions and language development. A quantitative approach with a quasi-experimental one-group pretest-posttest design was used. The study involved 30 parents at RA Qurratu A’yun Delitua, North Sumatra, selected through purposive sampling. The intervention included structured group sessions, role-playing exercises, individualized feedback, and follow-up monitoring. Data were collected using a validated and reliable skill scale and analyzed with paired sample t-tests. The results showed a significant improvement in parents’ social stimulation skills, with 80% in the high category post-intervention compared to 30% pre-intervention. These findings indicate that content mastery services effectively enhance parental skills. In the context of Islamic education, this intervention reinforces the family as the first madrasah, shaping children’s social, moral, and cognitive growth from early childhood.